VARIASI ARUS PENGELASAN SMAW TERHADAP KEKERASAN LOGAM LAS DAN HAZ MATERIAL BAJA ST 37 - Muh Anhar (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research aims to determine the effect of welding current on the hardness of weld metal and HAZ (heat affected zone) metal which is tested for hardness using the Rockwell method. This research was carried out on ST 37 low carbon steel material which was welded using an E6013 electrode with a diameter of 2.6 mm with a butt joint, then given different welding currents, namely 80, 100 Ampere. For specimens that were given a welding current of 80 Ampere, the average hardness of the weld metal obtained was 47.05 HRB and the HAZ was 50.3 HRB. Then the specimens that were welded with a current of 100 Ampere had an average weld metal hardness figure of 48.15 HRB and a HAZ of 50.5 HRB. The test results show that the increase in the hardness number in both the weld metal and the HAZ metal is directly proportional to the amount of current used when welding. The test results show that the increase in the hardness number in both the weld metal ) and in metal the HAZ is directly proportional to the amount of current used when welding.